STUDI PERBANDINGAN PERLAKUAN BAHAN BAKU DAN METODE DISTILASI TERHADAP RENDEMEN DAN KUALITAS MINYAK ATSIRI SEREH DAPUR (Cymbopogon citratus) - Slamet -; Supranto -; Riyanto - (ASEAN Journal of Systems Engineering, 2013)
Indonesia is rich in plant biodiversity. Indonesia volatile oil development efforts through increased development of one plant of lemon grass, which is one of the essential oil producing plants known as Cymbopogon citratus. Lemongrass essential oil in the chemical industry used as raw materials in the manufacture of cosmetics, perfume, deodorant, deodorant soap, floor cleaners and detergents.The purpose of this study was to determine the highest yield of lemongrass essential oil distillation using the method of water distillation, water-steam, and steam to the treatment of intact leaves and chopped leaves and know the quality of essential oil of lemongrass with the treatment of raw materials and different methods of distillation, the design used by two factors: variation in the treatment of raw material (whole leaves and chopped leaves) and the distillation process variation (distilled water (boiled), water-steam distillation and steam distillation. Data obtained from the analysis of yield, specific gravity, refractive index, and oil content of the compound citral essential (lemongrass oil).This study uses three methods of distillation, the distillation of water, water-steam distillation and steam distillation is carried out on samples of intact leaves and chopped leaves of fresh lemongrass. The results yield calculation and testing of physics and chemistry, as well as in the method of analysis SPSS One-Sample Test Statistics for the lemongrass essential oil products.Based on the  results of research on the treatment of raw materials and distillation methods can be concluded that the treatment of raw materials lemongrass intact leaves with water distillation method (boiled) at both the content yield 0.52%, 71.84% citral, specific gravity 0.8967 g/mL, and the refractive index of 1.4905. It is appropriate to mention that SNI 06-39-53-1995 yield 0.3%, the specific gravity of 0.8731 g/mL, and the refractive index of 1.4586. But the content of citral not meet SNI standards are 76.1%, but according to Guenther (2006) which states citral content of between 65% to 85%.